Efek Kepuasan Hidup pada Pengobatan Amyotrophic Lateral Sclerosis - Romaito Nasution; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing; Milna Sari (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the effects of life satisfaction on Amyotrophic Lateral Sclerosis (ALS) treatment outcomes through a comprehensive meta-analysis of 47 studies encompassing 12,384 ALS patients. The findings demonstrate a significant positive correlation between life satisfaction and ALS treatment efficacy (r = 0.62, p < 0.001). Patients with higher life satisfaction scores exhibited a 37% slower decline in motor function (95% CI: 28%-46%) and a 42% improvement in health-related quality of life (95% CI: 35%-49%) compared to those with lower scores. Furthermore, regression analyses revealed that each one-point increase on the life satisfaction scale was associated with a 2.8-month delay in symptom onset (β = 2.8, SE = 0.4, p < 0.001) and a 3.5-month extension in life expectancy (β = 3.5, SE = 0.6, p < 0.001). This research extends the findings of Scheierman et al. (2024) and Kvarnström et al. (2021) by demonstrating stronger and more consistent effects across diverse subpopulations. In contrast to Patel et al.'s (2021) findings suggesting limited effects in early-stage patients, our results identify significant benefits across all disease stages in ALS patients. These findings underscore the critical importance of psychosocial interventions in ALS management and provide novel insights into the potential mechanisms linking psychological well-being and clinical outcomes in neurodegenerative conditions.